Continuous descent operations in high throughput environment - Chan, Yong Cheng (2014)
This report attempted to simulate the fuel-minimal descent and approach trajectory of a single B747-400 aircraft under ISA conditions. The aircraft is modelled as a point-mass model with parameters taken from the BADA database of EUROCONTROL. The Hermite-Simpson method is used to discretize the optimal control problem and various constraints on the states and controls of the aircraft were imposed. Simulations conducted in 2D and 3D scenarios demonstrated clearly the ability of the aircraft to conserve fuel under continuous descent operation.